Costs, Energy Savings and Greenhouse Gas Emissions for Energy Efficiency Measures in Existing Detached Houses; A Norwegian Case Study - Anders-Johan Almås; Anne Sofie Bjelland; Geoffrey Sean Gilpin (Journal of Sustainable Development of Energy, Water and Environment Systems)

(untitled)
Energy efficiency measures for existing buildings are some of the most important actions towards reducing energy demand and greenhouse gas  emissions in society. Much is known regarding which measures provide the greatest energy savings, but this is rarely put into context with respect to costs and greenhouse gas emissions. This paper summarizes the results from a study comparing energy savings, greenhouse gas emissions and costs for energy efficiency measures in older detached houses. The paper presents and ranks the various energy efficiency measures regarding greenhouse gas emissions, energy savings and costs. The study concludes that the energy efficiency policy for existing buildings has not been successful. The study analyses why and provides recommendations on how the policy can be changed to achieve a greater effect.